2005
DOI: 10.1007/s10995-005-0036-0
|View full text |Cite
|
Sign up to set email alerts
|

Child Food Insecurity and Iron Deficiency Anemia in Low-Income Infants and Toddlers in the United States

Abstract: These findings suggest an association between child level food insecurity and iron deficiency anemia, a clinically important health indicator with known negative cognitive, behavioral and health consequences. Cuts in spending on food assistance programs that address children's food insecurity may lead to adverse health consequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
136
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 260 publications
(146 citation statements)
references
References 41 publications
8
136
0
2
Order By: Relevance
“…Paradoxically, in the United States, where levels of food insecurity are low, studies have reported that low-income children with food insecurity have twice the risk of presenting anemia compared to those with food security 28,29 , this being similar to data analyzed in India, a country that faces major socioeconomic inequalities 21 . This disparity in situations requires an analysis of the concept of the study variables and thus it is important to stress that iron deficiency anemia has a "pan-social" character that affects rich and poor countries; the main determinant of this nutritional deficiency is low intake of foods rich in iron and/or high physiological need, causing a negative balance in food consumption of the mineral and subsequently anemia 10 .…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…Paradoxically, in the United States, where levels of food insecurity are low, studies have reported that low-income children with food insecurity have twice the risk of presenting anemia compared to those with food security 28,29 , this being similar to data analyzed in India, a country that faces major socioeconomic inequalities 21 . This disparity in situations requires an analysis of the concept of the study variables and thus it is important to stress that iron deficiency anemia has a "pan-social" character that affects rich and poor countries; the main determinant of this nutritional deficiency is low intake of foods rich in iron and/or high physiological need, causing a negative balance in food consumption of the mineral and subsequently anemia 10 .…”
Section: Discussionsupporting
confidence: 52%
“…Dessa forma, a partir da última orientação da Organização Mundial da Saúde que indica como alternativa o uso de múltiplos micronutrientes em pó para a fortificação caseira 26 , foi formulado uma nova intervenção pelo governo brasileiro em parceria com instituições nacionais e internacionais, nomeada de NutriSUS, que visa melhorar o estado de ferro e reduzir a anemia em crianças entre 6-23 meses de idade 27 . Mesmo sabendo da eficácia dessa medida intervencionista 28 , a real efetividade ainda não foi avaliada, visto que o processo de implementação é recente. Contudo, pode-se dizer de forma simplista que essa é mais uma ação superficial para solucionar a questão de famílias de baixa renda "vítimas" da situação de anemia infantil, visto que as intervenções que não lidam com os determinantes distais da anemia são destinadas aos mesmos problemas enfrentados pelas estratégias intervencionistas já existentes.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…2 Adults in food-insecure households have a higher risk of inadequate nutrient intake, 3 as well as poorer self-rated health and an increased chance of developing diabetes, heart disease, hypertension and depression. 4 Children in food-insecure households are more likely to have poor overall health, 5,6 be diagnosed with iron deficiency anemia and asthma, 6,7 and have developmental and behavioural problems. 8 Alarmingly, childhood hunger has been associated with higher rates of depression, suicide ideation and suicide attempts in adolescence and early adulthood.…”
mentioning
confidence: 99%